Three new genera and eighteen new species of miniature polydesmid millipedes from the northwestern United States (Diplopoda, Polydesmida, Polydesmidae) - Shear, William A.; Marek, Paul E. (Zootaxa, 2021)
Three new genera, Retrorsioides, Rowlandesmus and Benedictesmus, are described and the polydesmid millipede fauna of North America is briefly reviewed with an emphasis on the genera Bidentogon Buckett & Gardner, 1968 and Retrorsia Shelley, 2003. Eighteen new species are described: Bidentogon buttensis, Bidentogon norcal, Retrorsia leonardi, Retrorsia benedictae, Retrorsia richarti, Retrorsia gracilis, Retrorsia simplicissima, Retrorsioides castellum, Retrorsioides linnensis, Retrorsioides kittitas, Retrorsioides bammerti, Retrorsioides arboramagna, Rowlandesmus millicoma, Rowlandesmus dentogonopus, Benedictesmus aureua, Benedictesmus ellenae, Benedictesmus yaquina and Benedictesmus timber. Natural history notes and illustrations are provided of putative commensal fungi, nematodes and a mite found on the millipede specimens.